Transition to violence: an evaluation of political parties and their move to terror - Danzell, Orlandrew E. (Kansas State University, 2011)
The goals of this dissertation are two-fold. First is to investigate and explain the key variables responsible for the process whereby political parties form alliances with or create terrorist organizations. Second is to fill an important gap in the literature by offering a more precise conceptualization of the issues and a different theoretical view. Extant literature argues that institutional structural constraints, such as electoral systems, are more likely to lead political parties to create terrorist organizations. However, this dissertation hypothesizes that regime ideology is also an important factor explaining the creation of terrorist organizations by political parties regardless of structural institutional constraints. This dissertation seeks to illuminate existing fears and concerns about alliances between terrorist groups and political parties in states whose ruling party platform is based on leftist, rightist, centrist, or religious ideology. Using empirical methods, which includes both quantitative and case study approaches, this dissertation intends to show that particular kinds of party ideology is positively correlated with the formation of terrorist organizations even after controlling for institutional structural constraints. The implication of these findings is important for policymakers eager to create stable polities.
Keywords: Terrorism; Electoral systems; Rightwing governments; Political parties; Political organization; Security studies; International Relations (0601); Political Science (0615)